"I Am Uncertain About What My Uncertainty Even Is": Men's Uncertainty and Information Management of Their BRCA‐Related Cancer Risks. Issue 6 (3rd July 2018) - Rauscher, Emily A.; Dean, Marleah; Campbell‐Salome, Gemme M.
Abstract: Men with a germline pathogenic BRCA1 or BRCA2 variant have increased risks for developing breast, pancreatic, prostate, and melanoma cancers, but little is known about how they understand and manage their cancer risks. This study examines how men with BRCA ‐ related cancer risks manage uncertainty and information about their risks. Twenty‐five men who were either a BRCA carrier or have a BRCA ‐ positive first‐degree family member that put the participant at 50% chance of also being a BRCA carrier were interviewed for this study. Using uncertainty management theory as a theoretical framework, this study demonstrates that men manage uncertainty by seeking information from female family members, websites, and healthcare providers, and are under‐informed about their cancer risks. Further, in handling their information, men prefer information about cancer risk percentages and screening recommendations in the form of lists presented to them via websites, printed literature, proactive healthcare providers, and an identifiable male spokesperson. Finally, men used BRCA‐related cancer risk information to make decisions about whether or not to engage in screening and prevention, manage their BRCA‐related cancer risks, and overall family well‐being—yet often at the expense of their own individual risks. Implications for genetic counseling and family conversations are discussed.